2003
DOI: 10.1093/ps/82.8.1215
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci affecting feather pecking behavior and stress response in laying hens

Abstract: In the European Union, legislation concerning animal housing is becoming stricter because of animal welfare concerns. Feather pecking (FP) in large group housing systems is a major problem. It has been suggested that corticosterone (CORT) response to manual restraint as a measure for stress is associated with FP behavior. The aim of the current study was to identify QTL involved in FP behavior and stress response in laying hens. An F2 population of 630 hens was established from a cross between two commercial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 34 publications
1
42
0
1
Order By: Relevance
“…Parent-of-origin effects have also been reported for QTL affecting the stress response and immune response . These two latter studies have been reported to be incorrect due to data handling error (Buitenhuis et al, 2006), but the parentof-origin effects have not yet been reanalyzed (van der Poel, personal communication).…”
Section: Qtl With Parent-of-origin Effectsmentioning
confidence: 99%
“…Parent-of-origin effects have also been reported for QTL affecting the stress response and immune response . These two latter studies have been reported to be incorrect due to data handling error (Buitenhuis et al, 2006), but the parentof-origin effects have not yet been reanalyzed (van der Poel, personal communication).…”
Section: Qtl With Parent-of-origin Effectsmentioning
confidence: 99%
“…Four microsatellite markers have been located within the chicken MHC-B region, LEI0258, MCW0371, MCW0312 and MHC-D (Buitenhuis et al, 2003;Crooijmans et al, 1997;Fulton et al, 2006;McConnell et al, 1999;Sironi et al, 2011), which can be effectively used to determine MHC-B haplotypes. Especially, LEI0258 marker genotypes could provide good indications of MHC-B haplotypes and can be used for preliminary screening in chicken populations (Chazara et al, 2013(Chazara et al, , 2011Fulton et al, 2006;Nikbakht et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…QTLs for basal corticosterone (Cort) levels have also been identified (20,25,27). However, only three studies, each in a different species, have investigated QTL for Cort in response to stress (9,13,29), and to date, no QTL studies have been done investigating adrenal gland weight and its relationship to stress.…”
mentioning
confidence: 99%